Harnessing mobile technology (MT) to enhancy the sustainable livelihood of rural women in Zimbabwe. case of mobile money transfer (MMT) - Musungwini, Samuel; Zhou, Tinashe G.; Zhou, Munyaradzi; Ruvinga, Caroline; Gumbo, Raviro (2016)
The focus of the study was to ascertain whether there is the existence of women money saving clubs in rural Zimbabwe, explore their operations and avail data which highlight the need for implementing tailor made Mobile Money Transfer (MMT) for all. These authors performed literature review to guide the research. To gather information these writers employed focus group discussion and survey questionnaires to extract information from the research participants. Participants of the survey research were women who were actively participating in money saving clubs in rural Zimbabwe. The focus group dialogue participants incorporated leaders of these rural women money saving clubs. This study will contribute to the body of knowledge novel information which is imperative for MMT operators in Zimbabwe. Therefore MMTs or Banks in Zimbabwe should embrace it.